Randomized Controlled Trial of Mindfulness-Based Therapy on Psychological Distress and Clinical Outcomes in Preeclampsia - Ernawati Ernawati; Kartika Sari Wijayaningsih; Andi Fajriansi; Nurafriani Nurafriani; Alfiah Alfiah; Hasifah Hasifah; Rusni Mato (Direktorat Politeknik Kesehatan Makassar, 2025)
Preeclampsia is one of the leading causes of maternal morbidity and mortality worldwide, often associated with psychological distress that worsens clinical outcomes. This study aimed to examine the effectiveness of Mindfulness-Based Therapy (MBT) on psychological distress and clinical outcomes in women with preeclampsia. A randomized controlled trial was conducted among 60 pregnant women diagnosed with preeclampsia who were randomly assigned into two groups: intervention (MBT + standard care) and control (standard care only). MBT was delivered in six sessions over three weeks, focusing on mindfulness breathing, body scanning, and acceptance strategies. Psychological distress was measured using the Depression Anxiety Stress Scale (DASS-21), while clinical parameters included systolic and diastolic blood pressure, and proteinuria level. The results showed a significant reduction in stress, anxiety, and depression scores (p < 0.05) in the intervention group compared to the control group. Clinically, the intervention group demonstrated better blood pressure control and reduced proteinuria. Mindfulness-Based Therapy effectively reduces psychological distress and improves clinical outcomes in preeclampsia. Integrating mindfulness interventions into antenatal care could enhance maternal well-being and pregnancy outcomes.